The Putatan Kadazans in a transitional period and their changes from their simple to a more complex society: A case study of the effects of the resultant changes / Helen Luin Richard - Helen, Luin Richard (1976)
Chapter I discusses the concepts and definitions used in the study. Overall, the Chapter deals mostly with the scope, general methodology employed and their weaknesses. The writer proposes to trace the process of change by comparing what members of the sample population of two generations ago (age 45 above) were, and what they and their children (age 30 below) are now. This is done by way of looking at the types of social, cultural, economic and politic institutions the former and the later participated in and are exposed to. She will therefore, first of all deal in Chapter II with the traditionalistic sot up the older generation were faced with. Next, she will discuss the period of transformation brought about by the facilities (external forces) introduced that have led to the motivation for change, both among the 45 and above group and even more so for the 30 and below group. This would for the most part be dealt with in Chapter III. The analysis of the impact of the facilities introduced and the resultant effects will be discussed in Chapter IV. It will mean giving an outline of the social, cultural, economic and political institutions that exist in the kampung today and comparing it with the facts dealt with in Chapter II. The concluding Chapter (Chapter V) will generally attempt to analyse the direction and trends of the change.